Effectiveness of a mobile application for reducing premarital sex risk factors among adolescents - Sunsanee Mekrungrongwong; Archin Songthap; Civilaiz Wanaratwichit (BMC Public Health)
Abstract Background Premarital sex results in an increase in unwanted pregnancy, abortion, and sexually transmitted diseases in adolescents. Premarital sex causes not only physical health but also mental health. This study aimed to assess the effectiveness of a mobile application for reducing premarital sex risk factors among adolescents in northern Thailand. Methods A quasi-experimental research with two groups pretest-posttest design was conducted between August and December 2023. The study sample consisted of 80 high school students studying at public secondary schools in Phisanulok Province, Thailand. They were divided into 2 groups, 40 for the experimental group and another 40 for the control group. The tools used in this study included (1) a mobile application for reducing risk factors of premature sex and (2) a questionnaire about the premarital sex risk factors which was employed for data collection. Data were analyzed using the mean, standard deviation, independent sample t-test, and paired t-test. Results The results showed that after using an application for reducing risk factors of premature sex, the experimental group had the mean risk factors of premature sex significantly (p < 0.05) lower than the control group and before using the application. However, after the intervention, the mean scores of premarital sex risk factors of the control group were significantly (p < 0.05) higher than before the intervention. Conclusion We suggested that school administrators should encourage teachers to motivate students to use mobile applications to reduce the risk factors of premature sex. Moreover, students can utilize the mobile application to assess the risk and prevent premarital sex. This application can be applied to teenagers in other areas that have a similar context to prevent premarital sex and its consequences.